Patient Satisfaction Surveys in the Outpatient Clinic Setting: The Variability of Response With Positively or Negatively Toned Questions - Brittany Saldivar BS; Carolyn Carter MD; Stephanie L. Filipp MPH; Matthew J. Gurka PhD; Michael K. Davis MD, MBA (SAGE Publishing, 2019)
The purpose of this study was to determine whether a patient satisfaction survey in the outpatient clinic setting using questions with either a positive or negative tone would produce consistent responses. This was a prospective study using a 20-question paper survey delivered to medical students who were asked to rate on a scale of 1 to 10 to what degree they either agree or disagree with statements regarding their most recent personal outpatient clinic health care visit (any medical specialty). The same survey was administered again through an e-mail link 1 week later. One hundred fifty (77%) students completed the 20-item survey and 53 (35%) of the participating students completed the follow-up e-mail survey. Seven of the 10 question pairs on the paper survey revealed statistically significant differences in responses based on tone, with greater values for disagreement with negatively toned questions than values representing agreement with positive-toned questions. The match rates for similar questions posed on the paper survey and then the e-mail survey 1 week later ranged between 27.8% and 56.6%. This study demonstrated that, with an outpatient health care patient satisfaction survey, disagreement with a negative-toned question was stronger than agreement with a positive-toned question. There was poor correlation between survey responses when first posed on a paper survey and then repeated on a digital survey 1 week later. These findings suggest that the wording of survey questions may affect responses and that survey answers change with time and across delivery platforms.